A review on the elemental contents of Pakistani medicinal plants: Implications for folk medicines. (21st July 2016) - Aziz, Muhammad Abdul; Adnan, Muhammad; Begum, Shaheen; Azizullah, Azizullah; Nazir, Ruqia; Iram, Shazia
Abstract: Ethnopharmacological relevance: Substantially, plants produce chemicals such as primary and secondary metabolites, which have significant applications in modern therapy. Indigenous people mostly rely on traditional medicines derived from medicinal plants. These plants have the capacity to absorb a variety of toxic elements. The ingestion of such plants for medicinal purpose can have imperative side effects. Hence, with regard to the toxicological consideration of medicinal plants, an effort has been made to review the elemental contents of ethno medicinally important plants of Pakistan and to highlight the existing gaps in knowledge of the safety and efficacy of traditional herbal medications. Materials and methods: Literature related to the elemental contents of ethno medicinal plants was acquired by utilizing electronic databases. We reviewed only macro-elemental and trace elemental contents of 69 medicinal plant taxa, which are traditionally used in Pakistan for the treatment of sundry ailments, including anemia, jaundice, cancer, piles, diarrhea, dysentery, headache, diabetes, asthma, blood purification, sedative and ulcer. Results: A majority of plants showed elemental contents above the permissible levels as recommended by the World health organization (WHO). As an example, the concentrations of Cadmium (Cd) and Lead (Pb) were reportedly found higher than the WHO permissible levels in 43 and 42 medicinal plants, respectively. More specifically, the concentrations of Pb (54 ppm: Silybum marianum ) and Cd (5.25 ppm: Artemisia herba-alba ) were found highest in the Asteraceae family. Conclusions: The reported medicinal plants contain a higher amount of trace and toxic elements. Intake of these plants as traditional medicines may trigger the accumulation of trace and toxic elements in human bodies, which can cause different types of diseases. Thus, a clear understanding about the nature of toxic substances and factors affecting their concentrations in traditional medicines are essential prerequisites for efficacious herbal therapeutics with lesser or no side effects.